The secular realm as interfaith space : discourse and practice in contemporary multicultural nation-states - Hedges, Paul (2020)
While classically posited as the separation of religion from public life, it is suggested that the contemporary secular public sphere in multicultural contexts has become a habitat for interfaith dialogue. Looking at dynamics in classical secular theory as well as some recent theorists of secularism and multiculturalism, most particularly Jürgen Habermas, Charles Taylor, Tariq Modood, and Rajeev Bhargava, it is shown that far from being hostile to religion much of the practice of secularism is often entwined with particular discourses of religious norms. Using spatial theory, especially that of Lefebvre, four cameos from the UK, USA, Singapore, and India are used as indicative of the way that interfaith discourse is embedded in various aspects of the secular public sphere from governmental, through official Non-Governmental Organisations (NGOs), to grassroots levels such that as forum externum religion is accepted in this space as interfaith dialogue. It is argued that a conceptual linkage of interfaith motifs is, if not inherent, then at least embedded in the secular realm in the contemporary multicultural context.